Implementation of Democratic Leadership Style at PT. Garindo Sejahtera Abadi - Ansari, Janwaroh Hasbi; Mochammad Isa Anshori (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Leadership is the process of getting other people to understand and agree on what needs to be done and how to do the task effectively. In a company, of course, company leaders apply different leadership styles. Type of leadership style used by PT. Garindo Sejahtera Abadi is democratic leadership. This article discusses the implementation of a democratic leadership style in PT. Garindo Sejahtera Abadi, this article aims to provide comprehensive and detailed insight into the implementation of democratic leadership implemented at PT. Garindo Sejahtera Abadi. The research method used is theoretical studies, previous literature, interviews and field observations. The discussion uses theory according to Gouzali Syadan in (Suradji & Martono, 2014). The research findings are the implementation of democratic leadership in PT. Garindo Sejahtera Abadi has been running very well